Filling with the Spirit as Dynamic Relationship - Williams, David T. (The expository times, 2011)
While it is clear that all Christians have received the Holy Spirit, many traditions, especially the Pentecostal, insist that there is an experience subsequent to conversion. While the work of the Spirit in justification enables a relationship to Christ, a second experience is enlivening, and primarily related to sanctification. This may be understood in terms of “filling”, which can be simultaneous with conversion, but should be repeated.